Origins of Plague and Cholera according to the Lithuanian Folklore - Skujytė-Razmienė, Asta (Tautosakos darbai, 2016)
The article aims at establishing the ways that folklore texts reflect the notions of plague and cholera, and how their connections with different elements and nature forces, the dissemination means attributed to them, their manifestations and modes of movement reveal the origins of these epidemic diseases. Texts on plague and cholera are far from numerous in the Lithuanian folklore; besides, the existing ones, rather than describing historic facts or symptoms of the disease, focus on recording emotions, thus presupposing painful traumatic experiences. E. g.: God forbid seeing what we saw. It is much better dying than walking among the dead. Wherever you step, there are lots of corpses (LMD I 144/33/) Unaware of the true reasons behind the emerging epidemic diseases, people looked for explanations in their surroundings and behavior, thus attempting to guess the origins of plague and cholera. According to the causes of appearance, it is possible to divide the folkbelief legends about plague into two groups. In the first group, the emergence and activity of the plague is related to the divine wrath and punishment; in the second, the subject responsible for the occurring disaster is sought out and attempted to stop. The legends and beliefs belonging to the first group are rather scarce; the image of plague as the divine wrath, which is popular in the European tradition, seems not so well established in the Lithuanian folk mentality. The plague in Lithuanian folklore is associated with mythical beings (witches, sorcerers) and can be perceived as result of their magic actions. According to the legends, the witches spread plague into the space inhabited by humans using air as means of dissemination. There is lack of information regarding the space from which the epidemic diseases allegedly originate. The folk-belief legends sometimes hint that the place from which plague emanates could have been imagined as situated in a supernatural space, although this space may contain elements similar to those of the human landscape, or associated to certain places that used to be perceived as intermediate points between the human world and the underworld. This notion is supported by the Lithuanian healing charms mentioning banishment of the disease from the human world into another, dead world, which would presuppose similarity of this space and the underworld. Associations between the epidemic diseases and the underworld are visible also in the outward appearance of the plague and cholera in the folk-belief legends: these diseases are depicted as females of different age, dressed in white or black, thus being close to the Reaper, the walking dead or spirits. Also functionally, diseases may be associated to the Reaper. However, there is a quantitative difference, since the very word plague (maras in Lithuanian) implies mass demise. Such effect of the epidemic disease is likely to have inspired appearance of one or several new mythical beings. It is important to note that deities of plague or cholera act autonomously in the folk-belief legends, while the Reaper becomes their companion performing the acts of mortifying. According to the texts from various periods (from the 15th until the 20th century), plague could have spread also by means of the revived dead. The motive of the malevolent dead is rather popular in folklore. Such uninvited visitors used to be eliminated by digging out the corpses and cutting off the heads. This was also practiced during the epidemics, in order to repress the plague. Another means of tempering the epidemic included burying of the living people or certain things (like locks). Connections between the underworld and the epidemic diseases are also reflected in the folk-belief legends describing people surviving the epidemics. As a rule, the survivors included people related to the sphere of death in one way or another, like makers of coffins or buriers of the dead. The diseases were also likely to show mercy on those who helped them: showed them the way or treated them to tobacco. Thus, the analysis of the folk-belief legends from the 19th–21st centuries about the plague and cholera reveals two possible interpretations of the causes for these epidemic diseases: the appearance of the plague is regarded either as the God’s punishment or as the result of the magical actions of the mythical beings. In both cases, air is the medium that diseases use to travel from their world into the human world. The appearance of the anthropomorphic shape of the disease deities is likely to be rooted in the need of the people to explain the numerous sudden deaths caused by the epidemics. The discussion of the most frequent motives from the folk-belief legends and charms allow for establishing special connections between the epidemic diseases and the underworld, further supported by the functional and outward similarities between the plague, cholera and the Reaper. Further comparison of the folk-belief legends and the ancient written sources illustrating the possible use of the dead to spread the infection, and the texts describing the survivors of the epidemics enables to conclude that plague and cholera could have been perceived in the Lithuanian folklore as originating from the underworld.